Adobe Photoshop CC learn by video - McCathran, Kelly (Peachpit Press, 2013)
"This training program from Adobe Press combines high-definition video with a printed reference guide to teach the fundamentals of Photoshop CC. Experienced instructor Kelly McCathran present a comprehensive introduction to Photoshop, including best practices as well as fundamental photography and image editing concepts. Covered topics include Photoshop's 3D improvements, Adobe Camera Raw 8, and how to work within the Creative Cloud. Crucial to the training are optimized teaching methods, practical tips, and the focus on learning by doing with project files."--Resource description page.
Title from resource description page (viewed August 30, 2013)
Keywords: Adobe Photoshop; Photography -- Digital techniques; Image processing -- Digital techniques; Photographie numérique; Traitement d'images; Techniques numériques; digital imaging; Image processing; Digital techniques; Photography; Digital techniques